Przemiany podziału pracy w rodzinach chłopskich - Nowak, Waldemar (Wydział Prawa i Administracji UAM, 1988)
Work in peasants' families is of twofold significance: productive and social. Social significance consists in work being entangled into the system of family roles played by particular members of a group. Each individual in a family plays a given role determined by his/her sex, age and place in the family structure. Productive activities are integral parts of those roles. Thus there is an entanglement of productive and family roles. It is a characteristic feature of peasants' families, absent in other types of families. The said entanglement is a factor of integral unity of a family. The development of the agricultural services sector brings about a loss of a part of peasants' occupational independence what in turn is connected with the changes in the traditional distribution of work in a family. External interferences into matters of a farm, into work relationships, are always interferences into the life of a family, into its structure.
Changes in work distribution in peasants' families